Performance and cardiac evaluation before and after a 3-week training camp for 400-meter sprinters - An observational, non-randomized study - Skalenius, M.; Mattsson, C. M.; Dahlberg, P.; Bergfeldt, L.; Ravn-Fischer, A. (PLOS ONE, 2019)
Objective: To study the performance and cardiovascular function after a 3-week training camp in athletes competing in an anaerobically dominant sport. Methods: Twenty-three competitive 400-m athletes were enrolled in this non-randomized study, 17 took part in a 3-week training camp in South-Africa (intervention), but one declined follow-up assessment, while 6 pursued in-door winter training in Sweden and served as controls. Electrocardiography, transthoracic echocardiography, blood test analyses, maximal exercise tolerance test, and a 300-m sprint test with lactate measurements ([La]peak) were performed before and after the training camp period. Results: At baseline, there were no clinically significant pathological findings in any measurements. The training period resulted in improved 300m-sprint performance [n = 16; running time 36.71 (1.39) vs. 35.98 (1.13) s; p<0.01] and higher peak lactate values. Despite 48% more training sessions than performed on home ground (n = 6), myocardial biomarkers decreased significantly (NT-pro BNP -38%; p<0.05, troponin T -16%; p<0.05). Furthermore, resting heart rate (-7%; p<0.01) and left ventricular systolic and diastolic volumes decreased -6% (p<0.01) and -10% (p<0.05), respectively. Conclusions: Intense physical activity at training camp improved the performance level, likely due to improved anaerobic capacity indicated by higher [La]peak. There were no clinically significant adverse cardiac changes after this period of predominantly anaerobic training.